A trait‐based approach to community assembly: partitioning of species trait values into within‐ and among‐community components - D. D. Ackerly; W. K. Cornwell (Ecology Letters, 2007)
Plant functional traits vary both along environmental gradients and among species occupying similar conditions, creating a challenge for the synthesis of functional and community ecology. We present a trait‐based approach that provides an additive decomposition of species’ trait values into alpha and beta components: beta values refer to a species’ position along a gradient defined by community‐level mean trait values; alpha values are the difference between a species’ trait values and the mean of co‐occurring taxa. In woody plant communities of coastal California, beta trait values for specific leaf area, leaf size, wood density and maximum height all covary strongly, reflecting species distributions across a gradient of soil moisture availability. Alpha values, on the other hand, are generally not significantly correlated, suggesting several independent axes of differentiation within communities. This trait‐based framework provides a novel approach to integrate functional ecology and gradient analysis with community ecology and coexistence theory.